2013
DOI: 10.2298/vsp1310940n
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial characteristics and motivational factors in woman seeking cosmetic breast augmentation surgery

Abstract: Differences in marital status, educational level, habitation and employment status were statistically insignificant, but there was a significantly lower body mass index (BMI) in the operated women. Considering motives for surgery, a few factors were distinguished: desire to feel more feminine (82.2%), confident (75.5%) and attractive (73.3%), to feel less shy with men (64.4%), to improve their sex life (46.5%), teasing history (42.2%) and easier to find a partner (11.1%) and job (2.2%). Both groups demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
4
13
0
5
Order By: Relevance
“…Similar to our findings, Golshani et al applied SCL‐90‐R scale to cosmetic surgery patients (rhinoplasty, blepharoplasty, face/jaw implant, mammoplasty, and liposuction) and found that GSI, hostility, interpersonal sensitivity, and anxiety scores of patients were statistically significantly higher than the control group. Nikolic et al designed a prospective study including a total of 45 augmentation mammaplasty patients and used “The Rosenberg's Self‐Esteem Scale” and they found self‐esteem scores of patients were lower than in the control group . In another study with augmentation mammaplasty patients, divorce rate, which might be a sign of depression or hypomania, was found to be higher among patients than healthy controls .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Golshani et al applied SCL‐90‐R scale to cosmetic surgery patients (rhinoplasty, blepharoplasty, face/jaw implant, mammoplasty, and liposuction) and found that GSI, hostility, interpersonal sensitivity, and anxiety scores of patients were statistically significantly higher than the control group. Nikolic et al designed a prospective study including a total of 45 augmentation mammaplasty patients and used “The Rosenberg's Self‐Esteem Scale” and they found self‐esteem scores of patients were lower than in the control group . In another study with augmentation mammaplasty patients, divorce rate, which might be a sign of depression or hypomania, was found to be higher among patients than healthy controls .…”
Section: Discussionmentioning
confidence: 99%
“…Partiendo de ello, buscan sentirse más femeninas y atractivas, tener más confianza en sí mismas, sentirse menos tímidas con los hombres, mejorar su vida sexual, facilitar el encuentro de una pareja y conseguir un trabajo (Nikolic et al, 2013;Rubin et al, 2009). Por otro lado, los resultados coinciden con otras investigaciones que han concluido que suele predominar una insatisfacción con la imagen corporal (Acuña, 2010;Carrion, 2011;Pullido Garzón, 2015) y trastornos de la imagen corporal (como el trastorno dismórifco corporal) en sujetos que solicitan cirugía (Chung-Sheng et al, 2010;Dakanalis et al, 2013;Shridharani et al, 2010).…”
Section: Discussionunclassified
“…Con respecto al estado civil, una investigación concluyó que uno de los motivos que presentan las mujeres solteras para realizarse una mamoplastia de aumento era facilitar el encuentro de una pareja (Nikolic et al, 2013). Partiendo de este hallazgo podría pensarse que se encontrarían diferencias significativas entre mujeres solteras y casadas en función del nivel de motivación para realizar más cirugías estéticas siendo las primeras, las solteras, las más motivadas.…”
Section: Discussionunclassified
See 2 more Smart Citations